PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KARET POLA SWADAYA KECAMATAN KUOK KABUPATEN KAMPAR - Manaek Ricardo Panjaitan; Eri Sayamar; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aims of this study were (1) to analyze the roles of socialization which have been implemented on rubber farming in Kuok Regency, (2) to analyze the level of farmers empowerment on private rubber farming on Kuok Regency, (3) to analyze relationship between the role of socialization and the empowement of rubber farmers on Kuok Regency. Samples were collected using purposive sampling method on Kuok Regency. There were 50 private rubber farmers as samples. The data were analyzed using double regretion. The analysis results showed that (1) agricultural socialization on rubber farmer activity in Kuok Regency has been quite affected. The role of socialization with education, disemination, consultation and supervision were categorized as quite affected while the role of fasilitation, monitoring and evaluation on socialization were less affected. (2) The empowerment of self- private rubber farmers on Kuok Regency was categorized less affected. The empowerment could be found on productive economics which categorized well affected while the farmers empowerment from human resources and farmers institutional on Kuok Regency was not effected significantly by education, disemination, fasilitation, consultation, supervision. Evaluation and monitoring were well affected but not significantly on empowerment of rubber farmers.Keywords: Socialization, empowerment, rubber farmers, self-helped